A fly ash-based radiation cooling coating and preparation method thereof
By using radiation refrigeration coatings made of fly ash, thermal conductivity agents, reflectors and other materials, the problem of high materials in the prior art is solved, and a low-cost and efficient radiation refrigeration effect is achieved, which is suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411367901.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The micro-nano metal materials used in existing radiation refrigeration coatings are expensive, resulting in high cost of coatings and are not suitable for large-scale industrial production and application.
Fly ash is used as the main raw material, and radiation refrigeration coatings are made by adding thermal conductivity and reflectors, and fly ash with specific pores and particle sizes are made by ball milling and calcining, thereby improving the radiation characteristics of the coatings.
It reduces the cost of raw materials, solves the problem of waste cinder reuse, is suitable for large-scale industrial production, and the coating has high radiation characteristics in the mid-infrared band, achieving good radiation refrigeration effect.
Smart Images

Figure CN119101379B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a fly ash-based radiation cooling coating and a preparation method thereof. Background Art
[0002] Coal is one of the most widely used fuels in the world today. At present, coal consumption accounts for more than half of my country's energy structure and is still the most important energy material. However, the coal slag produced after coal combustion is mainly disposed of by landfill, abandonment and accumulation, which not only occupies land, but also releases sulfur-containing gases to pollute the atmosphere, harm the environment, and even spontaneously ignite. Since the 20th century, countries around the world have gradually conducted research on the comprehensive utilization of coal slag, such as using it to design and make building materials, but there are still objective problems such as poor mechanical properties and difficulty in meeting construction needs.
[0003] At present, with the increasingly serious "greenhouse effect", extreme hot weather lasts longer and covers a wider range. People's demand for refrigeration has risen sharply. At present, refrigeration energy consumption accounts for about 20% of the world's total building electricity consumption and 10% of the world's total electricity consumption. It is often accompanied by the use of Freon, which damages the ozone layer. Improving the efficiency of existing refrigeration systems and exploring new refrigeration technologies have become urgent tasks. Sky radiation cooling technology refers to the process in which objects on the earth's surface emit infrared radiation to the universe through the "atmospheric window" band (mainly 8-13μm) to achieve self-cooling. Since the cosmic background is close to an ideal black body spectrum with a temperature of 2.7K, and the average temperature of the earth's surface is about 290K, the infrared radiation from the earth to the universe can be used to cool objects on the earth's surface. Ideally, 150W / m 2 energy radiation.
[0004] In recent years, with the development of nanophotonics and metamaterials, new spectrally selective radiation cooling materials have been rapidly developed. These new radiation cooling materials have high reflectivity in the solar radiation band and high emissivity in the "atmospheric window" band, which can achieve all-day radiation cooling. As a cooling technology that does not require energy input, sky radiation cooling can provide a new idea for coping with energy crises and global warming.
[0005] For example, a Chinese patent with publication number CN110684463A provides a radiation cooling coating and its application, which uses titanium dioxide doped with metal ions as a filler, assisted by fillers such as aluminum hydroxide, aluminum oxide and specific film-forming substances to make a radiation cooling coating, which can radiate heat in the 8-13μm band, and has an average reflectivity of 90% or more for the entire band of sunlight, and has excellent radiation cooling effect.
[0006] Another example is a Chinese patent with publication number CN115785809B, which provides a radiation cooling coating and a radiation cooling product thereof, which achieves efficient radiation cooling effect by adding two hollow microspheres and utilizing the reflection effect of the two hollow microspheres on sunlight of different wavelengths, and bonding the two microspheres by resin material. However, the radiation cooling coatings in the above-mentioned prior art all use expensive micro-nano metal materials, resulting in high cost of the prepared coatings, which cannot be industrially produced and used on a large scale. Summary of the invention
[0007] The invention provides a fly ash-based radiation cooling paint and a preparation method thereof, which are simple to prepare and have a wide range of material sources, and solve the technical problems of existing fly ash solid waste treatment and radiation cooling paint production costs being high and not suitable for industrial production and application.
[0008] Firstly, the present invention provides a fly ash-based radiation cooling paint, which comprises the following components by weight: 30 to 35 parts of fly ash, 15 to 20 parts of adhesive, 4 to 8 parts of thermal conductor, 12 to 16 parts of reflector and 30 to 40 parts of ethanol.
[0009] Furthermore, the coal ash particle size is 1 to 50 μm, the porosity is 45% to 50%, and the specific surface area is 25 to 30 m 2 / g, and the reflectivity at 400-800nm is 40-70%.
[0010] Furthermore, the adhesive comprises an acrylate adhesive and a polyurethane adhesive, and the mass ratio of the acrylate adhesive to the polyurethane adhesive is 2:1.
[0011] Furthermore, the thermal conductor is graphite powder or boron nitride powder, and the reflector is titanium dioxide, aluminum oxide or silicon dioxide powder.
[0012] The present invention also provides a method for preparing a fly ash-based radiation cooling coating, comprising the following steps:
[0013] Step 1, preparing fly ash: adding water to the recovered waste coal slag and grinding it into uniform particles, then heating and calcining the ground particles for the first time, and then heating and calcining them for the second time to form fly ash after natural cooling; Step 2, preparing coating: adding ethanol solution to the stirring kettle, rotating the stirring kettle to add the fly ash prepared in step 1, and then adding acrylic adhesive and polyurethane adhesive in sequence after evenly dispersing, keeping stirring and continuing to add thermal conductive agent and reflective agent and continue stirring until the materials are evenly mixed, and after evenly mixing, filtering through a sieve to obtain coating.
[0014] Furthermore, in the step 1, a ball mill is used to grind the waste coal slag, the ball-to-material water ratio during grinding is 1.6:1:0.6, and the grinding time is 1 to 3 hours.
[0015] Furthermore, in the step 1, the heating rate of the first heating calcination is 6-10°C / min, the calcination temperature is 800-1000°C, and the calcination time is 2-3h; the heating rate of the second heating calcination is 6-10°C / min, the calcination temperature is 1100-1300°C, and the calcination time is 2-3h.
[0016] Furthermore, in the step 2, the volume concentration of the ethanol solution is 15%, and the rotation speed of the stirring kettle is 500-1000 rpm.
[0017] Furthermore, in the step 2, the continuous stirring time is 2 to 3 hours, and the screen size is greater than or equal to 400 meshes.
[0018] Beneficial effects of the present invention:
[0019] 1. The present invention uses waste coal slag as the main raw material, and prepares the radiation cooling coating by adding a thermal conductor and a reflector, thereby enhancing the vibration characteristics of Si-O and Al-O bonds in fly ash, and adding an oxygen-containing organic solvent with a suitable vibration peak position, so that the radiation cooling coating has high radiation characteristics in the mid-infrared band. At the same time, the present invention prepares fly ash with specific pores and particle sizes through ball milling and calcination treatment, ensuring that the radiation cooling coating can have high reflectivity in the visible light band.
[0020] 2. The present invention uses waste coal slag as the main raw material. Compared with the expensive micro-nano metal particles or various complex composite microspheres used in the prior art, the raw material price is cheap and the problem of waste coal slag recycling is solved, which is suitable for large-scale promotion and use. At the same time, the preparation process of the radiation cooling coating of the present invention is simple, does not involve complex and expensive equipment and processes, and is very suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a physical picture of the fly ash sample prepared in Example 1 of the present invention;
[0022] Figure 2 This is a physical picture of the fly ash-based radiation cooling coating sample prepared in Example 1 of the present invention;
[0023] Figure 3 This is a reflection spectrum diagram of the fly ash-based radiation cooling coating prepared in Example 1 of the present invention;
[0024] Figure 4 This is the emission spectrum of the fly ash-based radiation cooling coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] Example 1
[0026] This embodiment provides a fly ash-based radiant cooling paint, comprising the following components by weight: 32 parts of fly ash, 15 parts of binder, 6 parts of thermal conductor, 12 parts of reflector and 35 parts of ethanol. The fly ash has a particle size of 1 to 50 μm, a porosity of 47%, and a specific surface area of 26 m 2 / g. The adhesive includes an acrylate adhesive and a polyurethane adhesive. In this embodiment, an acrylate emulsion adhesive and an aqueous polyurethane adhesive are used, and the mass ratio of the acrylate adhesive to the polyurethane adhesive is 2:1. The thermal conductor is graphite powder or boron nitride powder, and the reflector is titanium dioxide, aluminum oxide or silicon dioxide powder.
[0027] This embodiment also provides a method for preparing a fly ash-based radiation cooling coating, comprising the following steps:
[0028] Step 1, preparing fly ash: adding water to the recovered waste coal slag and grinding it into uniform particles, then heating and calcining the ground particles for the first time, and then heating and calcining them for the second time after natural cooling to form fly ash;
[0029] Specifically, the recycled waste coal slag is added to a ball mill, and water is added thereto for wet grinding to ensure that the ball-to-water ratio is 1.6:1:0.6. After grinding for 3 hours, the waste coal slag is ground into fine particles with uniform particle size. The waste coal slag particles are added to a crucible, and the crucible is covered with a lid and placed in a muffle furnace for heating and calcining. The heating rate is set to 10°C / min per minute to constantly increase the temperature to 1000°C, and the temperature is naturally cooled to room temperature after calcining for 2 hours.
[0030] The waste coal slag particles cooled to room temperature are put into the muffle furnace again, and the crucible cover is removed to heat and calcine. The heating rate is set to 10℃ / min and the temperature is constantly raised to 1200℃. After calcination for 2 hours, the temperature is naturally lowered to room temperature to produce fly ash.
[0031] Step 2, prepare the coating: add ethanol solution to the stirring kettle, rotate the stirring kettle and add the fly ash prepared in step 1, add acrylic adhesive and polyurethane adhesive in sequence after evenly dispersing, keep stirring and continue to add thermal conductor and reflector and continue stirring until the materials are evenly mixed, after evenly mixing, filter through a sieve to obtain the coating.
[0032] Specifically, add an ethanol solution with a volume concentration of 15% into a stirring kettle, then add the fly ash prepared in step 1, keep the stirring rate in the stirring kettle at 1000 r / min and keep stirring for 10 minutes to make it evenly dispersed. Then add an acrylic adhesive and a polyurethane adhesive at once, keep stirring for 10 minutes, then add graphite powder and titanium dioxide particles, continue stirring for 1 hour, filter the mixture through a sieve, and pour it out to obtain a fly ash-containing radiation cooling coating.
[0033] Example 2
[0034] The difference between this embodiment and embodiment 1 is that the heating rates of the first and second temperature-raising calcinations in step 1 are 8° C. / min, and the other experimental steps and experimental parameters are consistent with those in embodiment 1.
[0035] Example 3
[0036] The difference between this embodiment and embodiment 1 is that the first heating calcination temperature in step 1 is 800° C., and the other experimental steps and experimental parameters are consistent with those in embodiment 1.
[0037] Example 4
[0038] The difference between this embodiment and embodiment 1 is that the second heating calcination temperature in step 1 is 1300° C., and the other experimental steps and experimental parameters are consistent with those in embodiment 1.
[0039] Example 5
[0040] The difference between this embodiment and embodiment 1 is that the ball mill grinding time in step 1 is 2 hours, and the other experimental steps and experimental parameters are consistent with those in embodiment 1.
[0041] Comparative Example 1
[0042] The difference between this comparative example and Example 1 is that the heating rates of the first and second temperature-raising calcinations in step 1 are 6° C. / min, and the other experimental steps and experimental parameters are consistent with those in Example 1.
[0043] Comparative Example 2
[0044] The difference between this comparative example and Example 1 is that the first heating calcination temperature in step 1 is 700° C., and the other experimental steps and experimental parameters are consistent with those in Example 1.
[0045] Comparative Example 3
[0046] The difference between this comparative example and Example 1 is that the first heating calcination temperature in step 1 is 1100° C., and the other experimental steps and experimental parameters are consistent with those in Example 1.
[0047] Comparative Example 4
[0048] The difference between this comparative example and Example 1 is that the second heating calcination temperature in step 1 is 1000° C., and the other experimental steps and experimental parameters are consistent with those in Example 1.
[0049] Comparative Example 5
[0050] The difference between this comparative example and Example 1 is that the second heating calcination temperature in step 1 is 1400° C., and the other experimental steps and experimental parameters are consistent with those in Example 1.
[0051] Comparative Example 6
[0052] The difference between this comparative example and Example 1 is that the ball mill grinding time in step 1 is 1 h, and the other experimental steps and experimental parameters are consistent with Example 1.
[0053] The reflectivity of the radiant cooling coatings prepared in the above examples and comparative examples at 400-800 nm and the emissivity at 8-13 μm were tested, and the experimental results are shown in Table 1 below.
[0054] Table 1: Example & Comparative Example Experimental Data Table
[0055]
[0056]
[0057] Analysis of experimental results: From the experimental results in the above table, it can be seen that the fly ash-based radiant cooling coatings prepared in the embodiments of the present invention have high reflectivity in the visible light region and good emissivity in the far infrared region, which can reach up to 94% and 90% respectively.
[0058] When the heating rate was reduced, the reflectivity and emissivity of the prepared fly ash-based radiant cooling coating decreased significantly. The main reason was that the heating rate was too slow, which resulted in the inability of the fly ash to form suitable voids and particle sizes, thus causing the performance of the coating to decrease.
[0059] When the first and second calcination temperatures are not high enough, the reflectivity and emissivity of the fly ash-based radiant cooling coatings produced are significantly reduced. The main reason is that the insufficient calcination temperature cannot form fly ash that meets the requirements, which leads to a decrease in the performance of the coating produced. When the calcination temperature is too high, the fly ash structure will collapse, thus affecting the subsequent performance.
[0060] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view. In addition, it should be understood that although this specification is described in accordance with the embodiments, it does not contain only one technical solution. This narrative of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in the embodiments can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A fly ash-based radiant cooling coating, characterized in that: The invention comprises the following components by weight: 30 to 35 parts of fly ash, 15 to 20 parts of binder, 4 to 8 parts of thermal conductor, 12 to 16 parts of reflector and 30 to 40 parts of ethanol. The fly ash has a particle size of 1 to 50 μm, a porosity of 45% to 50%, and a specific surface area of 25 to 30 m 2 / g, the reflectivity at 400-800nm is 40-70%, the adhesive comprises an acrylate adhesive and a polyurethane adhesive, the mass ratio of the acrylate adhesive to the polyurethane adhesive is 2:1, the thermal conductor is graphite powder or boron nitride powder, and the reflective agent is titanium dioxide, aluminum oxide or silicon dioxide.
2. A method for preparing a fly ash-based radiation cooling coating as claimed in claim 1, characterized in that: The following steps are involved: Step 1, preparing fly ash: adding water to the recovered waste coal slag and grinding it into uniform particles, then heating and calcining the ground particles for the first time, and then heating and calcining them for the second time to form fly ash after natural cooling; Step 2, preparing coating: adding ethanol solution to the stirring kettle, rotating the stirring kettle to add the fly ash prepared in step 1, and then adding acrylic adhesive and polyurethane adhesive in sequence after evenly dispersing, keeping stirring and continuing to add thermal conductive agent and reflective agent and continue stirring until the materials are evenly mixed, and after evenly mixing, filtering through a sieve to obtain coating.
3. The method for preparing a fly ash-based radiation cooling coating according to claim 2, characterized in that: In the step 1, a ball mill is used to grind the waste coal slag, the ball-to-material-water ratio during grinding is 1.6:1:0.6, and the grinding time is 2 to 3 hours.
4. The method for preparing a fly ash-based radiation cooling coating according to claim 3, characterized in that: In the step 1, the first heating rate of calcination is 8-10°C / min, the calcination temperature is 800-1000°C, and the calcination time is 2-3h; the second heating rate of calcination is 8-10°C / min, the calcination temperature is 1100-1300°C, and the calcination time is 2-3h.
5. The method for preparing a fly ash-based radiation cooling coating according to claim 2, characterized in that: In the step 2, the volume concentration of the ethanol solution is 15%, and the rotation speed of the stirring kettle is 500-1000 rpm.
6. The method for preparing a fly ash-based radiation cooling coating according to claim 5, characterized in that: The continuous stirring time in step 2 is 1 to 2 hours, and the screen size is greater than or equal to 400 meshes.
Citation Information
Patent Citations
Radiation refrigeration coating material and applications thereof
CN110684463A
Radiative cooling coatings and radiative cooling products
CN115785809B
Reflective thermal-insulation exterior wall coating
CN103555102A
Alkali-activated coal ash-based expansive type steel structure fireproof coating
CN108424673A